Targeted screening of an anti-inflammatory polypeptide from Rhopilema esculentum Kishinouye cnidoblasts and elucidation of its mechanism in alleviating ulcerative colitis based on an analysis of the gut microbiota and metabolites - Wang, Ziyan; Shi, Qiuyue; Feng, Ying; Han, Jiaojiao; Lu, Chenyang; Zhou, Jun; Wang, Zhonghua; Su, Xiurong (Food science and human wellness, 2024)
Ulcerative colitis (UC) is a recurrent inflammatory bowel disease that imposes a severe burden on families and society. In recent years, exploiting the potential of marine bioactive peptides for the treatment of diseases has become a topic of intense research interest. This study revealed the mechanism underlying the protective effect of the dominant polypeptide PKKVV (Pro-Lys-Lys-Val-Val) of Rhopilema esculentum cnidoblasts against DSS-induced UC through a combined analysis of the metagenome and serum metabolome. Specifically, the polypeptide composition of R. esculentum cnidoblasts was determined by matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF/TOF-MS). Molecular docking showed that the dominant peptide PKKVV could bind better with tumor necrosis factor-α (TNF-α) than the original ligand. Subsequent animal experiments suggested that PKKVV could modulate disorganized gut microorganisms in mice with UC; affect serum metabolites through the arachidonic acid, glycerophospholipid and linoleic acid metabolism pathways; and further alleviate UC symptoms. This study provides a reference for the comprehensive development of marine bioactive substances and nonpharmaceutical treatments for UC. [Display omitted]